THE INFLUENCE OF USING THINK PAIR SHARE TECHNIQUE ON THE STUDENTS IN WRITING RECOUNT TEXTAT SMP TUNAS PELITA BINJAI - Muhammad Hasan (Jurnal Sintaksis, 2019)
This final project is entitled The Effect of Using Think Pair Share Technique on Students’ Writing Recount Text. It was held in SMP Tunas Pelita Binjai. The objective of the study was to find Think-Pair-Share techniques effect on teaching students'. The population of this study was the eighth-grade students of SMP Tunas Pelita Binjai. The subject of the study was 36 students. There are two classes and each class consist of 18 students. There were six meetings in the research. One meeting was for the pre-test for each class, four meetings for teaching technique and another one meeting for the post-test for each class. The post-test was held in the last meeting. In the pre-test, the students were asked to write a recount text. The average of the students’ scores by Think-Pair-Share was 63.2, and the post-test was 77,2. The average of the students’ scores by Conventional Class was 62.6 and the post-test was 67,7. The result is 7.36 >5.1 > 2.92. It means that the Think-Pair-Share technique effect on teaching students, writing recount text. The more significant technique for this case is Think-Pair-Share is more significant than the Conventional Method. The study demonstrates that teaching and learning by following the Think-Pair-Share techniques can use in writing recount text. I hope this result is able be used by other teachers to enable students to write recount texts.